2010
DOI: 10.1093/aje/kwq175
|View full text |Cite
|
Sign up to set email alerts
|

Use of Aspirin and Other Nonsteroidal Antiinflammatory Medications in Relation to Prostate Cancer Risk

Abstract: Recent interest has focused on the role that inflammation may play in the development of prostate cancer and whether use of aspirin or other nonsteroidal antiinflammatory drugs (NSAIDs) affects risk. In a population-based case-control study designed to investigate the relation between these medications and prostate cancer risk, detailed exposure data were analyzed from 1,001 cases diagnosed with prostate cancer between January 1, 2002, and December 31, 2005, and 942 age-matched controls from King County, Washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 38 publications
4
77
0
4
Order By: Relevance
“…COX-2 decreases the production of antiangiogenic cytokine interleukin-12 and also elevates metalloprotein levels that improve the invasion of tumor vessels (Ohno et al, 2007;Kim et al, 2011). Epidemiological studies demonstrate a decline in the incidence of many types of cancer in long-term users of nonsteroidal anti-inflammatory drugs (NSAIDS) (Wong and Chan, 2007;Salinas et al, 2010;Cui et al, 2014). Also it has been shown that regular usage of NSAIDS and COX-2 inhibitors reduce the mortality for sporadic CRC (Steinbach et al, 2000).…”
Section: Effects Of a Multikinasementioning
confidence: 99%
“…COX-2 decreases the production of antiangiogenic cytokine interleukin-12 and also elevates metalloprotein levels that improve the invasion of tumor vessels (Ohno et al, 2007;Kim et al, 2011). Epidemiological studies demonstrate a decline in the incidence of many types of cancer in long-term users of nonsteroidal anti-inflammatory drugs (NSAIDS) (Wong and Chan, 2007;Salinas et al, 2010;Cui et al, 2014). Also it has been shown that regular usage of NSAIDS and COX-2 inhibitors reduce the mortality for sporadic CRC (Steinbach et al, 2000).…”
Section: Effects Of a Multikinasementioning
confidence: 99%
“…However, there is also information against this correlation with PC presentation profile 10 . At present, radiotherapy with HD addition is the standard of care in high-risk PC 44 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to higher relative efficacy between different ACs, there is evidence that aspirin, versus other ACs, is the main responsible in PC prevention as well as in its decreased mortality 10,12,20,39,63 . Although there are also studies that do not find a clear relationship with aspirin or its dose or length of administration 11,13,15,21,64 , there are also data on PC prevention and lower aggressiveness with acetaminophen (paracetamol) 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations